Market Entry Strategy of Casamundo GmbH to the Czech Market - Zapletalová, Veronika (2014)
The objective of this thesis is to select the most suitable market entry mode and create a marketing strategy for accommodation rental company Casamundo GmbH. Suggested strategy will be based on characteristics of the Czech market and consumers and will help the company to establish itself in the market. The thesis is divided into three parts. Theoretical part summarizes main concepts and frameworks focused on foreign market entry and marketing strategy creation. It is followed by introduction of Casamundo GmbH and analysis of external and internal environment that will serve as a base for evaluation of company's strengths and weaknesses. Last part summarizes results of survey conducted among Czech consumers. Based on all collected data market entry mode is then suggested and the marketing strategy including adjustment to marketing mix is proposed.